2013
DOI: 10.1080/10410236.2013.769832
|View full text |Cite
|
Sign up to set email alerts
|

Humor in Print Health Advertisements: Enhanced Attention, Privileged Recognition, and Persuasiveness of Preventive Messages

Abstract: This study tested the effect of humor in one particular type of print advertisement: the preventive health ads for three topics (alcohol, tobacco, obesity). Previous research using commercial ads demonstrated that individuals' attention is spontaneously attracted by humor, leading to a memory advantage for humorous information over nonhumorous information. Two experiments investigated whether the positive effect of humor can occur with preventive health ads. In Experiment 1, participants observed humorous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 40 publications
3
58
0
Order By: Relevance
“…One of the ways health care providers do this is through the use of humor, the use of amusing or comical anecdotes or stories that can result in positive affect in the client. In the context of health counseling, humor has been found to increase the persuasiveness of health messages [5], build rapport, increase satisfaction with the relationship between patients and providers, and increase trust between them [2]. Humor has also been shown to be important in establishing therapeutic alliance, which is the trust and belief that a client has in working with a counselor to achieve their goals [21].…”
mentioning
confidence: 99%
“…One of the ways health care providers do this is through the use of humor, the use of amusing or comical anecdotes or stories that can result in positive affect in the client. In the context of health counseling, humor has been found to increase the persuasiveness of health messages [5], build rapport, increase satisfaction with the relationship between patients and providers, and increase trust between them [2]. Humor has also been shown to be important in establishing therapeutic alliance, which is the trust and belief that a client has in working with a counselor to achieve their goals [21].…”
mentioning
confidence: 99%
“…Findings of prior investigations conducted on the effect of humour on the effectiveness of advertisements are hereby highlighted: [1] Humour enhances the amount of attention given to adverts (Blanc, N., Brigaud, E., 2014; Weinberger and Gulas, 1992 However, contrary to the results presented above, some studies speculate that humour in advertising may lower message comprehension and also found humorous commercials are no more effective than comparable serious messages (Fang, 2011;Duncan, Nelson, Frontczak, 1984). All the above stated results were obtained from researches conducted in western environments/cultures.…”
Section: Some Findings Of Prior Humour-advertisement Researches -mentioning
confidence: 99%
“…Humor has long been used in advertising (Eisend, 2009), and has shown to have the potential to be effective in print advertisements. Blanc and Brigaud (2014) found that participants viewed humorous print ads for longer than they viewed nonhumorous ads, and humorous ads were also recalled better and were more convincing. In a meta-analysis of humor in commercial advertising, Eisend (2009) found that the use of humor in advertising messages had significant positive impacts on attitude towards the ad and brand, attention, positive affect, and purchase intention, while it reduced source credibility.…”
Section: Humormentioning
confidence: 91%
“…While humor has been extensively studied in commercial marketing, there is less known about how humor functions in a health promotion context (Blanc & Brigaud, 2014). Although there has been a considerable amount of research on humor in messaging in public health, there has not been a systematic review or meta-analysis summarizing the findings of the field.…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation